(untitled) (E Conference Zone, 2022)
this article presents the most important social feelings of empathy, theoretical information about the important role of empathy in the formation of the child’s personality and in his life as a whole, and at the same time, with the help of empathy, the child learns to understand other people, their inner experiences, to understand the dignity of another person, to help